Risk of Recurrent Venous Thromboembolism in Patients with Cancer: An Individual Patient Data Meta-analysis and Development of a Prediction Model - Lanting, Vincent R.; Takada, Toshihiko; Bosch, Floris T. M.; Marshall, Andrea; Grosso, Michael A.; Young, Annie M.; Lee, Agnes Y. Y.; Di Nisio, Marcello; Raskob, Gary E.; Kamphuisen, Pieter W.; Büller, Harry R.; van Es, Nick (Thrombosis and Haemostasis, 2024)
About 7% of patients with cancer-associated venous thromboembolism (CAT) develop a recurrence during anticoagulant treatment. Identification of high-risk patients may help guide treatment decisions.To identify clinical predictors and develop a prediction model for on-treatment recurrent CAT.For this individual patient data meta-analysis, we used data from four randomized controlled trials evaluating low-molecular-weight heparin or direct oral anticoagulants (DOACs) for CAT (Hokusai VTE Cancer, SELECT-D, CLOT, and CATCH). The primary outcome was adjudicated on-treatment recurrent CAT during a 6-month follow-up. A clinical prediction model was developed using multivariable logistic regression analysis with backward selection. This model was validated using internal–external cross-validation. Performance was assessed by the c-statistic and a calibration plot.After excluding patients using vitamin K antagonists, the combined dataset comprised 2,245 patients with cancer and acute CAT who were treated with edoxaban (23%), rivaroxaban (9%), dalteparin (47%), or tinzaparin (20%). Recurrent on-treatment CAT during the 6-month follow-up occurred in 150 (6.7%) patients. Predictors included in the final model were age (restricted cubic spline), breast cancer (odds ratio [OR]: 0.42; 95% confidence interval [CI]: 0.20–0.87), metastatic disease (OR: 1.44; 95% CI: 1.01–2.05), treatment with DOAC (OR: 0.66; 95% CI: 0.44–0.98), and deep vein thrombosis only as an index event (OR: 1.72; 95% CI: 1.31–2.27). The c-statistic of the model was 0.63 (95% CI: 0.54–0.72) after internal–external cross-validation. Calibration varied across studies.The prediction model for recurrent CAT included five clinical predictors and has only modest discrimination. Prediction of recurrent CAT at the initiation of anticoagulation remains challenging.
Keywords: recurrent VTE; cancer; prediction